1999
DOI: 10.1080/00032719908542827
|View full text |Cite
|
Sign up to set email alerts
|

Modified H-Point Standard Addition Method and Logarithmic Function for the Spectrophotometric and Spectrodensitometric Determination of Hesperidin and Diosmin in Mixtures

Abstract: The similarity in the chemical structure of hesperidin and diosmin represents a difficulty in determining one or both of them when present together in pharmaceutical dosage forms. Different techniques were described in this article in order to determine each one of them without interference from the. other, or from other additives in the pharmaceutical dosage forms. 383 The first method utilized the zero-order and first-derivative techniques for the determination of hesperidin at 290 nm in which diosmin has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The Literature Review. According to the literature survey, it was found that few analytical methods such as UV [1][2][3][4][5], Fluorometric method [6], LC-method [7], LC-MS method [8], HPLC method [9,10], capillary electrophoresis [11], simple colorimetric method [12], thin layer chromatography (TLC) [13], and adsorptive stripping voltammetry [14] were reported for hesperidin and Diosmin. To our knowledge, no study related to the UV spectrophotometric method for the simultaneous estimation of hesperidin and diosmin has been reported in literature.…”
Section: Introductionmentioning
confidence: 99%
“…The Literature Review. According to the literature survey, it was found that few analytical methods such as UV [1][2][3][4][5], Fluorometric method [6], LC-method [7], LC-MS method [8], HPLC method [9,10], capillary electrophoresis [11], simple colorimetric method [12], thin layer chromatography (TLC) [13], and adsorptive stripping voltammetry [14] were reported for hesperidin and Diosmin. To our knowledge, no study related to the UV spectrophotometric method for the simultaneous estimation of hesperidin and diosmin has been reported in literature.…”
Section: Introductionmentioning
confidence: 99%
“…These methods include voltammetry, [11] thin-layer chromatography, [12] high performance liquid chromatography (HPLC), [13,14] Fourier transform infrared spectrometry, [15,16] and spectrodensitometry. [17] The methods based on modern instrumental techniques are sensitive, i.e., by the HPLC method, 50 ng diosmin per injection could be detected. [13] Some of these methods require expensive instruments and maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…Just one spectrophotometric method for determination of diosmin has been reported. [17] This is based on the derivative technique applied for the determination of diosmin and hesperidin in mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…Few analytical methods have been established for D determination and proposed for drug monitoring such as voltammetric [4], high performance liquid chromatography [5,6], thin-layer chromatography [7,8] or Fourier transform infrared spectrometry [9,10] and spectrophotometric methods [7]. Because there are sensitive, convenient and relatively inexpensive, most of visible spectrophotometric methods are preferred for pharmaceutical determination.…”
Section: Introductionmentioning
confidence: 99%